A systematic review of prospective evidence linking non-alcoholic fermented food consumption with lower mortality risk - Paveljšek, Diana; Pertziger, Eugenia; Fardet, Anthony; Panagiotakos, Demosthenes Basilis; Savary-Auzeloux, Isabelle; Adamberg, Signe; Peñas, Elena; Frias, Juana; Ntantou, Anastasia; Diamantoglou, Ioannis; Domínguez-Soberanes, Julieta; Louis, Sandrine; et al. (Frontiers in Nutrition, 2025)
Fermented foods are consumed worldwide and are increasingly being studied for their potential health benefits. Although their consumption is widespread, their association with long-term health outcomes such as mortality risk remains unclear. The aim of this systematic review was to assess the association between the consumption of fermented foods and risk of all-cause, cardiovascular, and cancer-related mortality in generally healthy adult populations in accordance with the European Food Safety Authority (EFSA) framework for the substantiation of health claims. A comprehensive literature search identified prospective cohort studies from 1970 to 2025 that investigated the association between fermented food consumption and mortality outcomes. Risk of bias was assessed using the Newcastle-Ottawa Scale, and strength of evidence was evaluated based on study quality, sample size, and precision within a structured narrative framework that also classified the direction of association across categories. A complementary non-systematic review examined the compositional characteristics, mechanisms of action, and potential health risks associated with fermented foods. Fifty-two cohort studies were included. Fermented milk products (including yogurt), chocolate, and fermented soy products (particularly natto) suggested a modest inverse association with all-cause and cardiovascular mortality. Cheese was associated with reduced all-cause mortality in some studies, but it showed inconsistent effect on cardiovascular mortality. The evidence for cancer-related mortality was weaker, although yogurt and fermented milk displayed some protective trends. Evidence from a single cohort suggested a potential reduction in all-cause mortality with fermented vegetable consumption, whereas fermented meat suggested no clear association with mortality. Biological plausibility was supported by fermentation-derived compounds such as bioactive peptides, polyphenols, isoflavones, natto-kinase, and vitamin K2. Habitual consumption of certain fermented foods may be associated with modest reductions in mortality risk, but the current evidence remains insufficient to support EFSA-approved health claims. Randomized controlled trials are essential to demonstrate causality. While long-term trials with mortality endpoints are not feasible, studies targeting intermediate outcomes linked to mortality offer a practical alternative. These should be complemented by observational studies to capture long-term, real-world associations. Together, such efforts support the objectives of the COST Action PIMENTO (CA20128) in building a more robust evidence base on fermented foods and health.Systematic review registrationThe protocol for this systematic review was registered with the Open Science Framework (OSF; registration ID: vg7f6; https://osf.io/vg7f6).